High-temperature Fischer-Tropsch synthesis iron-based catalyst, preparation method and application of high-temperature Fischer-Tropsch synthesis iron-based catalyst in olefin preparation
By using iron-based catalysts with porous iron-based core-based core-based core-based core-based structures of HZSM-5 shells in Fischer-Tropsch synthesis, the problem of excessive by-products in the prior art is solved, and the yield of olefins and the activity stability of the catalyst are improved.
Patent Information
- Application Number
- CN202510061624.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-15
- Publication Date
- 2025-04-25
AI Technical Summary
Existing iron-based catalysts produce too many by-products in Fischer-Tropsch synthesis, reducing the yield of the target olefin and increasing the cost of subsequent separation and purification.
A high-temperature Fischer-Tropsch synthetic iron-based catalyst is designed, using the core-shell structure of the porous iron-based core and the HZSM-5 shell. By activating carbon monoxide and hydrogen through the core, the shell selectively cracks long-chain olefins, converts them into low-carbon olefins, and inhibits methane generation.
The conversion rate and selectivity of the reaction are improved, the generation of by-products is reduced, and the formation of low-carbon olefins is stable, and the active life of the catalyst is extended.
Smart Images

Figure CN119869601A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of catalysts, and in particular to a high-temperature Fischer-Tropsch synthesis iron-based catalyst, a preparation method and application thereof in the preparation of olefins. Background Art
[0002] Fischer-Tropsch synthesis (FTS) is an important chemical process that converts carbon monoxide and hydrogen (synthesis gas) into liquid hydrocarbons (such as olefins, alkanes and aromatics). This process can produce liquid fuels from non-petroleum resources such as coal, natural gas or biomass, and is one of the key technologies for replacing petroleum resources. The Fischer-Tropsch synthesis reaction not only helps alleviate the energy crisis, but also helps protect the environment, especially in reducing greenhouse gas emissions and optimizing the energy structure.
[0003] Iron-based catalysts are widely used in the Fischer-Tropsch synthesis reaction, mainly due to their low cost and good selectivity for olefins and high-carbon hydrocarbons. Iron-based catalysts are usually composed of iron metal, iron oxide, iron hydroxide and other substances, and their catalytic performance is significantly affected by the composition, structure and morphology of the catalyst. Although iron-based catalysts have certain advantages in Fischer-Tropsch synthesis, their performance still faces challenges. The catalytic reaction of synthesis gas with iron-based catalysts will produce too many by-products (such as alkanes or long-chain hydrocarbons), which will reduce the yield of the target olefins and increase the cost of subsequent separation and purification.
[0004] Therefore, it is necessary to design a high-temperature Fischer-Tropsch synthesis iron-based catalyst, a preparation method and its application in the preparation of light olefins. Summary of the invention
[0005] The present invention overcomes the deficiencies of the prior art and provides a high-temperature Fischer-Tropsch synthesis iron-based catalyst, a preparation method and application thereof in the preparation of olefins.
[0006] To achieve the above object, the technical solution adopted by the present invention is: a high-temperature Fischer-Tropsch synthesis iron-based catalyst, comprising: a porous iron-based inner core and a HZSM-5 outer shell, forming an iron-based catalyst with a core-shell structure.
[0007] A method for preparing a high-temperature Fischer-Tropsch synthesis iron-based catalyst comprises the following steps:
[0008] Step S1, dissolving an iron-based compound in water to prepare an iron salt solution, and adding an auxiliary salt to mix evenly to obtain a mixed solution;
[0009] Step S2, the mixed liquid droplets and the alkaline solution are subjected to precipitation treatment in parallel, the precipitate is filtered, and washed with water until it is neutral;
[0010] Step S3, drying the treated precipitate, and calcining the dried precipitate at high temperature to form a porous iron-based core;
[0011] Step S4, placing the iron-based core in water, and successively adding silica sol and HZSM-5 molecular sieve, adjusting the pH value with nitric acid, and coating the iron-based core with a shell layer by high-speed stirring to obtain an iron-based material with a preliminary core-shell structure, and calcining the iron-based material with the core-shell structure;
[0012] Step S5, performing reduction pretreatment on the calcined iron-based material.
[0013] In a preferred embodiment of the present invention, in step S1, the iron-based compound is a soluble iron salt, which is dissolved in water and stirred for 10-15 minutes at a temperature of 25-40° C. to prepare a 1-3 mol / L iron salt solution.
[0014] In a preferred embodiment of the present invention, in step S1, the auxiliary salt comprises: manganese nitrate and copper nitrate; and the manganese nitrate and copper nitrate are dissolved in water respectively to obtain 1-3 mol / L manganese nitrate solution and copper nitrate solution;
[0015] The manganese nitrate solution, the copper nitrate solution and the iron salt solution are mixed in a molar ratio of 5-30:3-10:100 among the three salt solutions, and stirred for 20-30 minutes to obtain a mixed solution.
[0016] In a preferred embodiment of the present invention, in step S2, the alkaline solution is a 0.5-2 mol / L NH4OH solution, and the mixed solution is mixed with the NH4OH solution at a molar ratio of 1:1.5-2;
[0017] The precipitation treatment includes: titrating the mixed liquid droplets and the alkaline solution in parallel and controlling the titration speed so that the pH of the precipitation solution is controlled at 8-9, and the parallel precipitation time is controlled at 10-30 minutes, and stirring at a speed of 300-500 rpm;
[0018] The precipitate produced by the reaction was filtered and repeatedly washed with water until the pH of the filtrate was close to neutral.
[0019] In a preferred embodiment of the present invention, in step S3, the drying process comprises: evenly spreading the wet precipitate obtained in step S2, placing it in an oven, and drying it at a temperature range of 100-130° C. for 4-8 hours.
[0020] In a preferred embodiment of the present invention, in step S3, the dried composite precipitate is subjected to high temperature calcination, including: heating the precipitate to 450-650° C. at a heating rate of 2-10° C. and calcining for 3-8 hours.
[0021] In a preferred embodiment of the present invention, in the step S4, the weight ratio of the iron-based core, the silica sol (based on 25% by weight SiO2 content) and the HZSM-5 added is in the range of 100:20-50:5-20, the temperature is controlled at 50-70°C, the pH value is in the range of 3-6, and the silicon-aluminum ratio of the HZSM-5 is in the range of 150-300. Through step S4, the SiO2 component in the sol and the HZSM-5 are aggregated on the surface of the iron-based core, and a shell layer is formed on the surface of the iron-based core to obtain an iron-based material with a preliminary core-shell structure;
[0022] The iron-based material with a preliminary core-shell structure is calcined at a temperature range of 450-650°C for 3-4 hours.
[0023] In a preferred embodiment of the present invention, in step S5, the iron-based material with the preliminary core-shell structure cooled in step S4 is heated in a hydrogen atmosphere at a temperature range of 150-200°C for 1.5-2h for preliminary reduction, and the temperature is gradually increased to a temperature range of 300-350°C and heated for 6-8h for further reduction.
[0024] Application of a high-temperature Fischer-Tropsch synthesis iron-based catalyst in the preparation of olefins, characterized in that: the temperature of the Fischer-Tropsch reaction is 300-370°C, the reaction pressure is 1.0-4.0MPa, and the catalyst load is 3000-20000h -1 .
[0025] The present invention solves the defects existing in the background technology and has the following beneficial effects:
[0026] (1) The present invention provides a method for preparing a high-temperature Fischer-Tropsch synthesis iron-based catalyst. By configuring a porous iron-based core and a HZSM-5 shell, the iron-based catalyst forms a core-shell structure. The core is used to activate carbon monoxide and promote its hydrogenation reaction with hydrogen to generate hydrocarbon products, thereby promoting the dissociation of CO and the growth of CC chains. The shell is used to selectively crack long-chain olefins on the hydrocarbon products generated by the core to convert heavy hydrocarbons into light olefins. At the same time, methane generation is inhibited, product distribution is regulated, light olefins are generated stably, the conversion rate and selectivity of the reaction are improved, and the generation of by-products is effectively reduced.
[0027] (2) The present invention provides a HZSM-5 shell, and the microporous structure of the HZSM-5 shell limits the diffusion space of larger products, thereby reducing the generation of large molecular hydrocarbons and improving the yield of light olefins.
[0028] (3) The present invention provides protection for the iron-based core by providing a HZSM-5 shell, thereby preventing it from sintering and degradation under high temperature conditions, and avoiding the iron-based core from sintering and reducing active sites under high temperature conditions, resulting in loss of catalytic activity. At the same time, the HZSM-5 shell effectively prevents oxidation of the core, thereby ensuring that the core maintains a high catalytic activity for a long time.
[0029] (4) The present invention provides a HZSM-5 shell and utilizes the pores and acidic sites of the HZSM-5 shell to inhibit the secondary polymerization reaction of light olefins on the surface of the iron-based catalyst. The microporous structure of the HZSM-5 shell can selectively retain heavy hydrocarbons in the pores and convert them into light olefins through cracking, which helps to improve the yield of the target product, avoids the formation of high molecular weight waxes, and reduces the accumulation of long-chain alkanes during the cracking process. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art are briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention. For those of ordinary skill in the art, other drawings can be obtained based on these drawings without creative work.
[0031] Figure 1 The present invention is a flow chart of a method for preparing a high-temperature Fischer-Tropsch synthesis iron-based catalyst. DETAILED DESCRIPTION
[0032] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0033] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein. Therefore, the protection scope of the present invention is not limited to the specific embodiments disclosed below.
[0034] In the description of the present application, it should be understood that the terms "center", "longitudinal", "lateral", "up", "down", "front", "back", "left", "right", "vertical", "horizontal", "top", "bottom", "inside", "outside", etc., indicating the orientation or positional relationship, are based on the orientation or positional relationship shown in the drawings, and are only for the convenience of describing the present application and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as limiting the scope of protection of the present application. In addition, the terms "first", "second", etc. are only used for descriptive purposes, and cannot be understood as indicating or implying relative importance or implicitly indicating the number of technical features indicated. Therefore, features defined as "first", "second", etc. may explicitly or implicitly include one or more of the features. In the description of the invention, unless otherwise specified, "multiple" means two or more.
[0035] In the description of this application, it should be noted that, unless otherwise clearly specified and limited, the terms "installed", "connected", and "connected" should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be directly connected or indirectly connected through an intermediate medium, and it can be the internal communication of two components. For ordinary technicians in this field, the specific meanings of the above terms in this application can be understood by specific circumstances.
[0036] A high-temperature Fischer-Tropsch synthesis iron-based catalyst comprises a porous iron-based inner core and a HZSM-5 outer shell, forming an iron-based catalyst with a core-shell structure.
[0037] like Figure 1 As shown, a method for preparing a high-temperature Fischer-Tropsch synthesis iron-based catalyst comprises the following steps:
[0038] Step S1, dissolving an iron-based compound in water to prepare an iron salt solution, and adding an auxiliary salt to mix evenly to obtain a mixed solution;
[0039] Step S2, the mixed liquid droplets and the alkaline solution are subjected to precipitation treatment in parallel, the precipitate is filtered, and washed with water until it is neutral;
[0040] Step S3, drying the treated precipitate, and calcining the dried precipitate at high temperature to form a porous iron-based core;
[0041] Step S4, placing the iron-based core in water, and successively adding silica sol and HZSM-5 molecular sieve, adjusting the pH value with nitric acid, and coating the iron-based core with a shell layer by high-speed stirring to obtain an iron-based material with a preliminary core-shell structure, and calcining the iron-based material with the core-shell structure;
[0042] Step S5, performing reduction pretreatment on the calcined iron-based material.
[0043] In the present invention, in step S1, the iron-based compound is a soluble iron salt, which is dissolved in water and stirred for 10-15 minutes at a temperature of 25-40° C. to prepare a 1-3 mol / L iron salt solution, wherein the soluble iron salt is ferrous chloride;
[0044] In step S1, the auxiliary salt includes: manganese nitrate and copper nitrate;
[0045] Manganese nitrate: Manganese, as a catalyst additive, can enhance the oxygen reduction performance and high temperature resistance of the catalyst. Manganese plays a role in promoting electron transfer in the catalytic reaction, which helps to improve the catalytic activity and durability of the catalyst.
[0046] Copper nitrate: Copper ions, as additives, can help improve the selectivity of the catalyst. In the catalytic conversion reaction of carbon monoxide, copper has a strong adsorption capacity for CO and can promote the conversion of carbon monoxide into olefin products.
[0047] and dissolving manganese nitrate and copper nitrate in water respectively to obtain 1-3 mol / L manganese nitrate solution and copper nitrate solution;
[0048] The manganese nitrate solution, the copper nitrate solution and the iron salt solution are mixed in a molar ratio of 5-30:3-10:100 among the three salt solutions, and stirred for 20-30 minutes to obtain a mixed solution.
[0049] In the present invention, in step S2, the alkaline solution is a 0.5-2 mol / L NH4OH solution, and the mixed solution is mixed with the NH4OH solution at a molar ratio of 1:1.5-2;
[0050] The precipitation treatment includes: titrating the mixed liquid droplets and the alkaline solution in parallel and controlling the titration speed to 1-2 mL / min, controlling the pH of the precipitation solution to 8-9, and controlling the parallel precipitation time to 10-30 min, and stirring at a speed of 300-500 rpm;
[0051] The addition of alkaline solution will cause the metal salts of iron, manganese and copper to precipitate as hydroxides from the solution, and the metal ions will gather together in the form of their hydroxides to form a composite precipitate;
[0052] The composite precipitate produced by the reaction is filtered and repeatedly washed with water until the pH of the filtrate is close to neutral, ensuring that excess ammonia and dissolved nitrates are removed.
[0053] In the present invention, in step S3, the drying process comprises: spreading the composite precipitate obtained in step S2 evenly, placing it in an oven, and drying it at a temperature range of 100-110° C. for 4-8 hours.
[0054] In the step S3, the dried composite precipitate is subjected to high-temperature calcination, including: heating the precipitate to 450-650° C. at a heating rate of 2-10° C. and calcining for 3-8 hours.
[0055] In the present invention, in the step S4, the weight ratio of the iron-based core, the silica sol (based on 25% by weight SiO2 content) and the HZSM-5 added is in the range of 100:20-50:5-20, the temperature is controlled at 50-70°C, the pH value is in the range of 3-6, and the silicon-aluminum ratio of the HZSM-5 is in the range of 150-300. Through step S4, the SiO2 component in the sol and the HZSM-5 are aggregated on the surface of the iron-based core, and a shell layer is formed on the surface of the iron-based core to obtain an iron-based material with a preliminary core-shell structure;
[0056] The iron-based material with a preliminary core-shell structure is calcined at a temperature range of 450-650°C for 3-4 hours.
[0057] Silica sol mainly provides SiO2 components, which serves to provide a layer of HZSM-5 shell for the iron-based core, which helps to prevent the sintering of the iron-based core or the loss of active sites, while improving the stability of the catalyst; the pH value range of 3-6 helps the stable aggregation of SiO2 components and also helps the dispersion of ZSM-5, ensuring that both can be evenly coated on the surface of the iron-based core to form a shell.
[0058] The iron-based inner core obtained by high-temperature calcination is placed in water, and silica sol and HZSM-5 molecular sieve are added successively. The surface active sites on the surface of the iron-based inner core will interact with the SiO2 component in the sol, and the SiO2 component will be deposited on the surface of the inner core through physical adsorption and chemical reaction to form a shell layer;
[0059] During this process, the temperature is controlled between 50-70°C, so that SiO2 and HZSM-5 in the sol can be evenly deposited on the surface of the core, while avoiding premature gelation of silicate at too high a temperature. The SiO2 sol gradually polymerizes on the surface of the iron-based core. With the deposition of HZSM-5 and SiO2, a layer of HZSM-5 shell with a thickness of 5-10nm gradually forms on the surface of the iron-based core. At this time, the iron-based catalyst already has a preliminary "core-shell structure", that is, the iron-based core is covered by the HZSM-5 shell.
[0060] After the coating process is completed, the iron-based material with a preliminary core-shell structure is calcined at 450-650°C for 3-4 hours to ensure that HZSM-5 and SiO2 are effectively combined and stabilized on the surface of the iron-based core, complete the solidification of the shell layer, and make it firmly attached to the surface of the iron-based core, so that the structure of HZSM-5 is stable, ensuring that it maintains a microporous structure and has the required acidic sites.
[0061] The iron-based core coated with the HZSM-5 shell is calcined at high temperature to further enhance the stability of the HZSM-5 shell, so that it can be better combined with the surface of the iron-based core to form a solid core-shell structure. At the same time, the possible residual solvent can be removed during the calcination process, thereby improving the purity and activity of the catalyst;
[0062] After calcination, the bond between the HZSM-5 shell and the iron-based core becomes stronger, forming a stable core-shell structure, which can not only effectively isolate the catalytic active sites of the core, but also improve the thermal stability of the catalyst.
[0063] In step S4, the prepared HZSM-5 shell can effectively isolate the direct contact between the iron-based core and the external reactants, thereby preventing the iron-based catalyst from being affected by oxidation and corrosion. The HZSM-5 shell can also prevent the deactivation of the iron core under high temperature or strong acid or strong alkali environment;
[0064] The microporous structure and acidic sites of the HZSM-5 shell can effectively inhibit the formation of by-products. The acidic sites of the shell contribute to the selective formation of olefins and reduce the formation of low-carbon products by limiting the diffusion path of smaller molecules. At the same time, the microporous structure of the HZSM-5 shell provides more diffusion space for larger products, thereby reducing the formation of large molecular hydrocarbons and increasing the yield of low-carbon olefins.
[0065] The HZSM-5 shell provides protection for the iron-based core, preventing it from sintering and degradation under high temperature conditions, avoiding sintering and reduction of active sites in the iron-based core under high temperature conditions, leading to loss of catalytic activity. At the same time, the HZSM-5 shell effectively prevents oxidation of the core, thereby ensuring that the core maintains a high catalytic activity for a long time.
[0066] The pores and acidic sites of the HZSM-5 shell inhibit the secondary polymerization reaction of light olefins on the surface of the iron-based catalyst. The microporous structure of the HZSM-5 shell can selectively retain heavy hydrocarbons in the pores and convert them into light olefins through cracking, which helps to improve the yield of the target product and avoid the formation of high molecular weight waxes. At the same time, it reduces the accumulation of long-chain alkanes during the cracking process.
[0067] In the present invention, in step S5, the iron-based material with the preliminary core-shell structure cooled in step S4 is heated in a hydrogen atmosphere at a temperature range of 150-200°C for 1.5-2h for preliminary reduction, and the temperature is gradually increased to a temperature range of 300-350°C and heated for 6-8h for further reduction.
[0068] The content ratio of SiO2 will affect the effect of the core-shell structure. The effect of the content ratio of SiO2 on the effect of the core-shell structure iron-based catalyst is studied.
[0069] Experimental example
[0070] 1. Testing of catalysts in Fischer-Tropsch synthesis
[0071] A. Reaction conditions:
[0072] Temperature: 400°C; CO / H2 ratio: 1:2; reaction pressure: 20 bar; reaction time: 24 hours; feed gas flow rate: 50 mL / min.
[0073] B. Steps:
[0074] loading the catalyst into the reactor and pre-reducing the catalyst;
[0075] The feed gas and CO conversion were analyzed by gas chromatography with a thermal conductivity detector (TCD), and the hydrocarbon product selectivity was analyzed by gas chromatography with a hydrogen flame ionization detector (FID).
[0076] C. Evaluation indicators:
[0077] This experiment requires calculation and analysis of the raw gas conversion rate and product selectivity. The area normalization method is used for calculation, and the calculation formula is as follows:
[0078] (1) Actual CO conversion rate:
[0079]
[0080] Note: CO in ——The molar amount of CO actually flowing into the reactor;
[0081] CO out ——The molar amount of CO actually discharged from the reactor.
[0082] Reaction product selectivity:
[0083]
[0084] Note: Wi——Hydrocarbons with content i in the product;
[0085] 2. Experimental steps
[0086] Embodiment 1:
[0087] Dissolve ferrous chloride (derived from Shanghai Yuanye Biotechnology Co., Ltd., model AR, molecular weight 198.81) in water, and stir for 15 minutes at a temperature of 35°C to prepare a 1 mol / L iron nitrate solution; dissolve manganese nitrate (derived from Shandong Zhengxing New Materials Co., Ltd., purity specification 50%) and copper nitrate (derived from Hubei Tosoh Chemical Technology Co., Ltd., purity specification 99%) in water to obtain 1 mol / L manganese nitrate solution and copper nitrate solution respectively; mix the manganese nitrate solution, copper nitrate solution and iron salt solution in a molar ratio of 15:5:100 of the three salt solutions, and stir for 30 minutes to obtain a mixed solution;
[0088] The mixed droplets and the alkaline solution (1% NH4OH solution, from Mitachieve, product number MIT-HB9790) flowed in parallel at a rate of 2 mL / min, and stirred at a rate of 500 rpm. The addition of the alkaline solution will cause the metal salts of iron, manganese and copper to precipitate as hydroxides, which will aggregate together in the form of their hydroxides to form a composite precipitate. The composite precipitate produced by the reaction was filtered and repeatedly washed with water until the pH of the filtrate was close to neutral.
[0089] The dried composite precipitate is calcined at high temperature, including: heating the precipitate to 550°C at a heating rate of 5°C / min and calcining for 3-8 hours to form a microspherical porous iron-based core with a particle size of 45±5nm and a pore size of 4±2nm;
[0090] An iron-based core, silica sol (based on 25% by weight SiO2 content) and HZSM-5 (derived from Sigma-Aldrich, brand 51490) are added in a weight ratio range of 100:20:10 and mixed, and the calcined iron-based core is immersed in the sol, and the temperature is controlled at 70°C to polymerize the SiO2 component in the sol to form a 6±1nm thick HZSM-5 shell on the surface of the iron-based core to obtain an iron-based material with a preliminary core-shell structure, and the iron-based material with the preliminary core-shell structure is calcined at a temperature range of 500°C for 4h;
[0091] The cooled iron-based material with a preliminary core-shell structure is heated in a temperature range of 200°C for 2 hours for preliminary reduction, and the temperature is gradually increased to a temperature range of 350°C and heated for 8 hours for further reduction to obtain an iron-based catalyst with a core-shell structure.
[0092] Embodiment 2:
[0093] The method is substantially the same as the embodiment, except that the iron-based core, silica sol (based on 25% by weight SiO2 content) and HZSM-5 are mixed in a weight ratio of 100:25:10, the calcined iron-based core is immersed in the sol, the temperature is controlled at 70°C, the SiO2 component in the sol is polymerized, and a 6±1 nm thick HZSM-5 shell is formed on the surface of the iron-based core to obtain an iron-based material with a preliminary core-shell structure, and the iron-based material with the preliminary core-shell structure is calcined at a temperature range of 500°C for 4h;
[0094] The cooled iron-based material with a preliminary core-shell structure is heated in a temperature range of 200°C for 2 hours for preliminary reduction, and the temperature is gradually increased to a temperature range of 350°C and heated for 8 hours for further reduction to obtain an iron-based catalyst with a core-shell structure.
[0095] Embodiment three:
[0096] The method is substantially the same as the embodiment, except that the iron-based core, silica sol (based on 25% by weight SiO2 content) and HZSM-5 are mixed in a weight ratio of 100:30:10, the calcined iron-based core is immersed in the sol, the temperature is controlled at 70°C, the SiO2 component in the sol is polymerized, and a 6±1 nm thick HZSM-5 shell is formed on the surface of the iron-based core to obtain an iron-based material with a preliminary core-shell structure, and the iron-based material with the preliminary core-shell structure is calcined at a temperature range of 500°C for 4h;
[0097] The cooled iron-based material with a preliminary core-shell structure is heated in a temperature range of 200°C for 2 hours for preliminary reduction, and the temperature is gradually increased to a temperature range of 350°C and heated for 8 hours for further reduction to obtain an iron-based catalyst with a core-shell structure.
[0098] Embodiment 4:
[0099] The method is substantially the same as the embodiment, except that the iron-based core, silica sol (based on 25% by weight SiO2 content) and HZSM-5 are mixed in a weight ratio of 100:35:10, the calcined iron-based core is immersed in the sol, the temperature is controlled at 70°C, the SiO2 component in the sol is polymerized, and a 6±1 nm thick HZSM-5 shell is formed on the surface of the iron-based core to obtain an iron-based material with a preliminary core-shell structure, and the iron-based material with the preliminary core-shell structure is calcined at a temperature range of 500°C for 4h;
[0100] The cooled iron-based material with a preliminary core-shell structure is heated in a temperature range of 200°C for 2 hours for preliminary reduction, and the temperature is gradually increased to a temperature range of 350°C and heated for 8 hours for further reduction to obtain an iron-based catalyst with a core-shell structure.
[0101] Embodiment five:
[0102] The method is substantially the same as the embodiment, except that the iron-based core, silica sol (based on 25% by weight SiO2 content) and HZSM-5 are mixed in a weight ratio of 100:40:10, the calcined iron-based core is immersed in the sol, the temperature is controlled at 70°C, the SiO2 component in the sol is polymerized, and a 6±1 nm thick HZSM-5 shell is formed on the surface of the iron-based core to obtain an iron-based material with a preliminary core-shell structure, and the iron-based material with the preliminary core-shell structure is calcined at a temperature range of 500°C for 4h;
[0103] The cooled iron-based material with a preliminary core-shell structure is heated in a temperature range of 200°C for 2 hours for preliminary reduction, and the temperature is gradually increased to a temperature range of 350°C and heated for 8 hours for further reduction to obtain an iron-based catalyst with a core-shell structure.
[0104] Embodiment six:
[0105] The method is substantially the same as the embodiment, except that the iron-based core, silica sol (based on 25% by weight SiO2 content) and HZSM-5 are mixed in a weight ratio of 100:45:10, the calcined iron-based core is immersed in the sol, the temperature is controlled at 70°C, the SiO2 component in the sol is polymerized, and a 6±1 nm thick HZSM-5 shell is formed on the surface of the iron-based core to obtain an iron-based material with a preliminary core-shell structure, and the iron-based material with the preliminary core-shell structure is calcined at a temperature range of 500°C for 4h;
[0106] The cooled iron-based material with a preliminary core-shell structure is heated in a temperature range of 200°C for 2 hours for preliminary reduction, and the temperature is gradually increased to a temperature range of 350°C and heated for 8 hours for further reduction to obtain an iron-based catalyst with a core-shell structure.
[0107] Control group:
[0108] Dissolve ferrous chloride in water, and stir for 15 minutes at a temperature of 35°C to prepare a 1 mol / L iron nitrate solution; dissolve manganese nitrate and copper nitrate in water to obtain 1 mol / L manganese nitrate solution and copper nitrate solution respectively; mix the manganese nitrate solution, copper nitrate solution and iron salt solution in a molar ratio of 15:5:100, and stir for 30 minutes to obtain a mixed solution;
[0109] The mixed liquid droplets and the alkaline solution flowed in parallel at a rate of 2 mL / min and stirred at a rate of 500 rpm. The addition of the alkaline solution will cause the metal salts of iron, manganese and copper to precipitate as hydroxides. The metal ions will gather together in the form of their hydroxides to form a composite precipitate. The composite precipitate produced by the reaction is filtered and repeatedly washed with water until the pH of the filtrate is close to neutral.
[0110] The dried composite precipitate is calcined at high temperature, including: heating the precipitate to 550°C at a heating rate of 5°C / min and calcining for 3-8 hours to form a microspherical porous iron-based core with a particle size of 45±5nm and a pore size of 4±2nm;
[0111] The iron-based material is heated in a temperature range of 200°C for 2 hours for preliminary reduction, and the temperature is gradually increased to a temperature range of 350°C and heated for 8 hours for further reduction, the iron-based catalyst.
[0112] The performance of the iron-based catalysts obtained in Examples 1 to 6 and the control group was tested, as shown in Table 1.
[0113] Table 1
[0114]
[0115]
[0116] In summary, comparative example one to example six, can be drawn, as SiO2 content proportion increases, C2-C4 light olefin total yield increases, mainly because, SiO2 itself has relatively low acidity, will not provide strong acid sites like iron-based kernel, as SiO2 content increases, the number of catalyst surface strong acid sites decreases, suppresses the occurrence of excessive hydrogenation reaction, thereby reducing the generation of alkanes, and in catalytic reaction, SiO2 protects the particle structure of iron-based kernel, maintains the specific surface area of catalyst and the number of active sites. Higher specific surface area means more CO and H2 can react on the catalyst surface, promote the generation of light olefins, higher SiO2 content can optimize the pore structure of catalyst, make small molecules (such as CO and H2) can more effectively contact the active sites of iron-based catalyst, promote the synthesis of light olefins, as SiO2 content increases, the electron density on the surface of iron kernel gradually decreases, this reduces the excessive reduction reaction on Fe active site, makes iron-based catalyst can be more involved in the formation reaction of light olefins, instead of generating heavier alkanes.
[0117] However, as the proportion of SiO2 content continues to increase, the total yield of C2-C4 light olefins decreases. This is mainly because, as the SiO2 content increases, too much SiO2 may fill the pores of the catalyst, limiting the entry of low molecular weight reactants (such as CO and H2) into the active sites of the catalyst, thereby reducing the efficiency of the reaction and the yield of light olefins. The production of light olefins often requires the participation of mild acidic sites. Too much SiO2 may result in too few acidic sites, resulting in reduced selectivity for light olefins and an increased tendency to produce alkanes. Too few acidic sites may also reduce the overall efficiency of the catalytic reaction, further affecting the yield of light olefins.
[0118] By comparing Examples 1 to 6 and the control group, it can be concluded that the performance of the iron-based catalyst with a core-shell structure is higher than that of an ordinary iron-based catalyst, mainly because ordinary iron-based catalysts tend to have strong acidity and are easy to catalyze side reactions or unwanted reactions (such as alkane generation). By covering the surface of the iron-based catalyst with a shell layer of materials such as SiO2, the generation of alkanes can be inhibited, the generation of low-carbon olefins (such as C2-C4 olefins) can be promoted, and the selectivity of the reaction can be improved. In addition, the surface of SiO2 can affect the path of the reaction by adjusting the acid-base properties, further improving the selectivity of the catalyst for the target product.
[0119] In summary, embodiment 4 is the optimal solution of the present invention.
[0120] A high-temperature Fischer-Tropsch synthesis iron-based catalyst is used in the preparation of olefins. Carbon monoxide and hydrogen are compressed by a compressor and enter a high-temperature Fischer-Tropsch reactor. The iron-based catalyst is used to react under the catalytic action to obtain a logistics rich in olefins.
[0121] The above is based on the ideal embodiment of the present invention. Through the above description, relevant personnel can make various changes and modifications without departing from the technical concept of the present invention. The technical scope of the present invention is not limited to the content in the specification, and the technical scope must be determined according to the scope of the claims.
Claims
1. A method for preparing a high-temperature Fischer-Tropsch synthesis iron-based catalyst, characterized in that: The following steps are involved: Step S1, dissolving an iron-based compound in water to prepare an iron salt solution, and adding an auxiliary salt to mix evenly to obtain a mixed solution; Step S2, the mixed liquid droplets and the alkaline solution are subjected to precipitation treatment in parallel, the precipitate is filtered, and washed with water until it is neutral; Step S3, drying the treated precipitate, and calcining the dried precipitate at high temperature to form a porous iron-based core; Step S4, placing the iron-based core in water, and successively adding silica sol and HZSM-5 molecular sieve, adjusting the pH value with nitric acid, and coating the iron-based core with a shell layer by high-speed stirring to obtain an iron-based material with a preliminary core-shell structure, and calcining the iron-based material with the core-shell structure; Step S5, performing reduction pretreatment on the calcined iron-based material.
2. The method for preparing a high-temperature Fischer-Tropsch synthesis iron-based catalyst according to claim 1, characterized in that: In the step S1, the iron-based compound is a soluble iron salt, which is dissolved in water and stirred for 10-15 minutes at a temperature of 25-40° C. to prepare a 1-3 mol / L iron salt solution.
3. The method for preparing a high-temperature Fischer-Tropsch synthesis iron-based catalyst according to claim 1, characterized in that: In the step S1, the auxiliary salt includes: manganese nitrate and copper nitrate; and the manganese nitrate and copper nitrate are dissolved in water respectively to obtain 1-3 mol / L manganese nitrate solution and copper nitrate solution; The manganese nitrate solution, the copper nitrate solution and the iron salt solution are mixed in a molar ratio of 5-30:3-10:100 among the three salt solutions, and stirred for 20-30 minutes to obtain a mixed solution.
4. The method for preparing a high-temperature Fischer-Tropsch synthesis iron-based catalyst according to claim 1, characterized in that: In the step S2, the alkaline solution is a 0.5-2 mol / L NH4OH solution, and the mixed solution is mixed with the NH4OH solution at a molar ratio of 1:1.5-2; The precipitation treatment includes: titrating the mixed liquid droplets and the alkaline solution in parallel and controlling the titration speed so that the pH of the precipitation solution is controlled at 8-9, and the parallel precipitation time is controlled at 10-30 minutes, and stirring at a speed of 300-500 rpm; The precipitate produced by the reaction was filtered and repeatedly washed with water until the pH of the filtrate was close to neutral.
5. The method for preparing a high-temperature Fischer-Tropsch synthesis iron-based catalyst according to claim 1, characterized in that: In step S3, the drying process includes: evenly spreading the wet precipitate obtained in step S2, placing it in an oven, and drying it at a temperature range of 100-130° C. for 4-8 hours.
6. The method for preparing a high-temperature Fischer-Tropsch synthesis iron-based catalyst according to claim 1, characterized in that: In the step S3, the dried composite precipitate is subjected to high-temperature calcination, including: heating the precipitate to 450-650° C. at a heating rate of 2-10° C. and calcining for 3-8 hours.
7. The method for preparing a high-temperature Fischer-Tropsch synthesis iron-based catalyst according to claim 1, characterized in that: In the step S4, the weight ratio of the iron-based core, the silica sol (based on 25% by weight SiO2 content) and the HZSM-5 added is in the range of 100:20-50:5-20, the temperature is controlled at 50-70°C, the pH value is in the range of 3-6, and the silicon-aluminum ratio of the HZSM-5 is in the range of 150-300. Through step S4, the SiO2 component in the sol and the HZSM-5 are aggregated on the surface of the iron-based core, and a shell layer is formed on the surface of the iron-based core to obtain an iron-based material with a preliminary core-shell structure; The iron-based material with a preliminary core-shell structure is calcined at a temperature range of 450-650°C for 3-4 hours.
8. The method for preparing a high-temperature Fischer-Tropsch synthesis iron-based catalyst according to claim 1, characterized in that: In step S5, the iron-based material with the preliminary core-shell structure cooled in step S4 is heated in a hydrogen atmosphere at a temperature range of 150-200°C for 1.5-2h for preliminary reduction, and the temperature is gradually increased to a temperature range of 300-350°C and heated for 6-8h for further reduction.
9. A high temperature Fischer-Tropsch synthesis iron-based catalyst, characterized in that: include: A porous iron-based inner core and an iron-based catalyst forming a core-shell structure.
10. Use of a high-temperature Fischer-Tropsch synthesis iron-based catalyst in the preparation of olefins, characterized in that: The temperature of the Fischer-Tropsch reaction is 300-370°C, the reaction pressure is 1.0-4.0MPa, and the catalyst load is 3000-20000h -1 .